THE CHOICE OF METHOD OF SURGICAL TREATMENT OF OBESITY (review of literature) - Yu. I. Sedletsky; D. I. Vasilevsky (Вестник хирургии имени И.И. Грекова)
During the long history of obesity surgery and associated diseases, a large number of operation techniques with different mechanisms of action have been proposed. However, all currently existing options for surgical correction of obesity have their advantages and disadvantages, ultimately determining the results and side effects of treatment. This circumstance determines the exceptional importance of the correct choice of methods for bariatric surgery. The article considers the basic principles and criteria for choosing the method of surgical treatment of overweight and related diseases from different perspectives.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.